Everyday life and a sense of loneliness in the opinion of elderly persons with disabilities in long-term residential care - SZCZUPAŁ, BERNADETA; WIŚNIEWSKA, JOLANTA IZABELA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Bernadeta Szczupał, Jolanta Izabela Wiśniewska, Everyday life and a sense of loneliness in the opinion of elderly persons with disabilities in long-term residential care. Interdisciplinary Contexts of Special Pedagogy, no. 24, Poznań 2019. Pp. 11-25. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.24.01 The growing number of elderly people, including persons with disabilities, is a major social, economic and political challenge. The article presents the results of a qualitative research concerning the opinions of elderly persons with disabilities in long-term residential care, about their everyday life and the sense of loneliness experienced by them.